2006
DOI: 10.1002/arch.20119
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter 8 (GLUT8) from the red imported fire ant, Solenopsis invicta buren (Hymenoptera: Formicidae)

Abstract: We have cloned the fire ant glucose transporter 8 (GLUT8) cDNA providing the first molecular characterization of a GLUT8 in insects. Glucose is a poly-alcohol and, due to its high hydrophilicity, cannot move across cell membranes. GLUT8 is a putative facilitative transporter for the cellular import and export of glucose. The complete 2,974-bp cDNA encodes a 501-residue protein with a predicted molecular mass of 54.8 kDa. Transcripts were detected in the brain, midgut, hindgut, Malpighian tubule, fat body, ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
0
12
0
5
Order By: Relevance
“…A sugar transporter designated fire ant GLUT8 cDNA (GenBank accession no. AY911645) was recently isolated from the hymenopteran S. invicta (Chen et al, 2006), and this deduced sequence corresponded to Q2KKJ2_SOLIN in Pfam v22.0. A phylogenetic analysis revealed that the amino acid sequence of Q2KKJ2_SOLIN was more similar to that of TRET1 than to that of other sugar transporters, including human GLUT8 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A sugar transporter designated fire ant GLUT8 cDNA (GenBank accession no. AY911645) was recently isolated from the hymenopteran S. invicta (Chen et al, 2006), and this deduced sequence corresponded to Q2KKJ2_SOLIN in Pfam v22.0. A phylogenetic analysis revealed that the amino acid sequence of Q2KKJ2_SOLIN was more similar to that of TRET1 than to that of other sugar transporters, including human GLUT8 ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 91%
“…4A and B). In addition, the Hymenopteran fire ant GLUT8 transcripts mentioned above appeared more abundant in the fat body (Chen et al, 2006) and DmTret1-1 is abundant in the larval fat body according to FlyAtlas (keyword: CG30035). In insects, taking into account the physiological and biochemical roles of the fat body, where trehalose is synthesized (Becker et al, 1996), such tissue localizations provide strong evidence that TRET1 is involved in the facilitation of trehalose transport from the fat body into the haemolymph, thereby maintaining trehalose levels in the haemolymph.…”
Section: Discussionmentioning
confidence: 97%
“…The few initial studies (15,45,51,52) suggested the absence of sugar transporters in the insect gut and described the absorption as a passive, possibly diffusional, process sustained by the extremely rapid transformation of glucose into the disaccharide trehalose. However, functional and molecular studies have recently demonstrated that sugar transporters belonging to the GLUT family are present in insects of different orders (9,13,19,36,58), although their membrane localization in the absorbing cells has been reported only in one case (9).…”
Section: The Adult Females Of the Entomophagous Parasitoid Waspmentioning
confidence: 98%
“…Early studies with insect gut suggested that sugars were absorbed totally by diffusion without involving carrier proteins in the process (Treherne, 1957;Treherne, 1958). More recently, several studies involving both physiology and molecular biology have described a number of sugar transporters of the GLUT family in insects from several different orders (Caccia et al, 2005;Chen et al, 2006;Escher and RasmusonLestander, 1999;Pascual et al, 2006;Wang and Wang, 1993). The first report describing a detailed model for carrier-mediated sugar movement across an absorbing insect epithelium was published in 2007 (Caccia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%